The Effect of Kepel Fruit Extract on The Number of Spermatogenic Cells in Mice (Mus musculus) - Marwa Azzahra; I Wayan Merta; Kusmiyati Kusmiyati (Jurnal Biologi Tropis, 2023)
The Kepel plant (Stelechocarpus burahol) has garnered research interest due to its diverse secondary metabolites like alkaloids, flavonoids, polyphenols, saponins, triterpenoids, and quinones, thought to impact fertility. This research aims to determine the effect of kepel fruit extract on the number of spermatogenic cells in mice (Mus musculus), consisting of spermatogonia cells, spermatocyte cells, and spermatid cells. Employing a Posttest-Only Control Design, Kepel extraction used 95% ethanol via maceration. 25 mice were divided into groups: positive control, negative control, groups I, II, and III exposed to 50, 100, and 150 mg/kgBW Kepel extract for 36 days. Randomized group design determined sample selection, assessing seminiferous tubules via four fields of vision. Statistical analysis involved one-way ANOVA (5% significance) and LSD test for disparities. Data were analyzed using SPSS 25. ANOVA revealed no significant difference (p > 0.05) in mean spermatogonia and spermatocyte cell counts between control and treatment groups (I, II, III). However, groups I, II, and III exhibited significant spermatid cell reduction. In conclusion, Kepel fruit extract at 50 mg/kgBW, 100 mg/kgBW, and 150 mg/kgBW could lower spermatid cell count, indicating potential as an antifertility agent.